Deep brain stimulation and revising the Mental Health Act: the case for intervention-specific safeguards. (28th September 2018) - Pugh, Jonathan; Aziz, Tipu; Herring, Jonathan; Savulescu, Julian
Abstract : Under the current Mental Health Act of England and Wales, it is lawful to perform deep brain stimulation in the absence of consent and independent approval. We argue against the Care Quality Commission's preferred strategy of addressing this problematic issue, and offer recommendations for deep brain stimulation-specific provisions in a revised Mental Health Act. Declaration of interest: T.A. is a paid consultant for Boston Scientific, Medtronic and St. Jude Medical. He has received honoraria from Abbott, Boston and Medtronics and served as consultant to all three.